Construction of Self-Identity: “Blusukan” as the Strategy of Campaigning for Surakarta City Mayor Election - Gama, Betty; Sudardi, Bani; Abdullah, Wakit; Wijaya, Mahendra (Politika: Jurnal Ilmu Politik, 2021)
In political communication, “blusukan” (impromptu visit) is called door to door campaign, in which candidates conduct face-to-face communication by visiting the people directly. This situation creates personal intimacy in the sense of there is no physical distance and formal protocolary distance. People can see the personality of their candidate leaders closely. This face-to-face communication meeting can be interpreted that the candidates "nguwongke" (humanizing), putting the people not onto the context of profit-loss-based rational relation (between the electorate and the elected), but putting them as partners inseparable from the successful candidate leader. This study is based on fieldwork in Surakarta during the mayor election, applied in-depth interviews with politicians. While in ancient times the leader conducted "blusukan" to know his people’s condition, “blusukan” during the campaign for Mayor Election is conducted to socialize or to introduce the couples to the people. Having known the candidates, people are expected to think of whether or not they will elect them.